AI-Powered Language Learning: Blended Learning, Food and Nutrition Education, Academic Performance, Practical Skills, Digital Literacy, Socio-Demographic Variables, Philippines - Bale, Wilma; Delopere, Faith; Frenal, Jesamie (JPAIR Institutional Research, 2026)
Blended learning, which integrates face-to-face instruction with digital platforms, has emerged as a promising approach in food and nutrition education. The purpose of this review is to examine how blended learning influences student performance, focusing on academic outcomes, skill acquisition, and socio-demographic factors. A systematic search of peer-reviewed studies highlights evidence on achievement scores, competency development, and learner engagement. Results indicate that blended learning enhances academic performance by promoting flexibility, individualized pacing, and interactive content delivery. Students benefit from asynchronous access, multimedia resources, and improved knowledge retention compared to traditional instruction. It also fosters learner autonomy while maintaining instructor guidance. Skill acquisition in food preparation, dietary planning, and evaluation of nutrition information was strengthened when digital modules were combined with hands-on practice. Simulations, videos, and case studies helped learners apply concepts before laboratory activities. Collaborative learning through forums and group projects further enhanced communication and teamwork. Effectiveness varied across populations due to age, gender, socio-economic status, and access to technology. Younger students adapted quickly, while older learners needed support. Socio-economic disparities such as poor connectivity and limited devices created inequities, highlighting the need for institutional support. In the Philippine context, accelerated by the COVID-19 pandemic, access to technology and cultural attitudes strongly shaped success. Students with limited exposure struggled with self-directed learning, underscoring the need for orientation and technical support. Overall, blended learning improves knowledge, skills, and professional competencies but requires equitable access and contextual adaptation.